Actor-Centered, Problem-Based, Situated – Design-Based Development of the Company Case Study as a Teaching Method in Geography Education - Hiller, Jan (Journal of Geography Education, 2018)
The company case study establishes suitable frameworks for use as a teaching method which will assist the learning of economic geographic concepts on an inductive knowledge path. The theoretical framework is formed by employing postmodern, actorcentered Economic Geography approaches, along with concepts for the case study method. Therefore, the company case study can help overcome an unsolved practical problem of Geography Education: school-based Economic Geography is in an unsatisfactory situation. Economic Geography has so far hardly featured as a topic of Geography Education; Economic Geography education captures pupils' interest only to a very limited extent; the pluralism of paradigms in Economic Geography hinders the adaptation of new insights for school teaching; and ultimately, the position of Economic Geography within school subjects has not been conclusively clarified. The aim of this paper is to articulate the design-based development of the company case study. The cyclic-iterative research process uses design-based research (DBR) as a methodological framework and combines teaching development with empirical research. Design principles characterize the company case study as a teaching method. Throughout, a multi-stage process of operationalization concretizes the four abstract formulated design principles of actor centering, problem-based learning, situated learning and regional anchoring. The qualitative analysis of the learning process decodes the individual knowledge construction of central economic geographic concepts. The combination of problem centered interviews, videographed teaching experiments and several intermediate surveys creates a learning process that can be analyzed in sub-segments. The core result of the study is a so-called design framework, which contains the further developed design principles of the prototypical company case study, as well as consequences drawn from the learning process analysis. These consequences generalize the context-related results of the empirical surveys, in the form of statements about the structuring of learning processes, the economic geographic specificities of knowledge acquisition, and the role of the pupil's interest
Keywords: Economic Geography, case study, design-based research, learning process, teaching experiment